APOE genotype is associated with oral herpetic lesions but not genital or oral herpes simplex virus shedding - Koelle, David M; Magaret, Amalia; Warren, Terri; Schellenberg, Gerard D; Wald, Anna (Sexually transmitted infections, 2010)
BackgroundApolipoprotein E is polymorphic in the human population. APOE4 has previously been reported to correlate with symptomatic oral and genital herpes disease.MethodsAPOE was genotyped in 182 subjects with herpes simplex virus (HSV) 2 and in 62 subjects with HSV-1, including 44 subjects with both viral types for a total of 200 adults. HSV shedding was measured by PCR from swab samples obtained daily from mucosa for at least 30 days. Participants also maintained a diary of oral or genital lesions.ResultsThe APOE genotypes observed reflected the US white population and the Hardy–Weinberg equilibrium. Genital and oral HSV shedding was detected on 17.2% and 3.7% of overall days, respectively, whereas genital and oral lesion rates were 10.1% and 2.9%. Using Poisson regression and adjusting for known correlates of HSV shedding, a significant association was not observed between the APOE genotype and genital or oral HSV shedding, or genital HSV lesions. However, the presence of the APOE4 allele was associated with a higher rate of oral herpetic lesions, with a relative risk of 4.64 (95% CI 1.32 to 15.05, p=0.016).ConclusionsVariation at the APOE locus may be associated with clinical manifestations of HSV-1 infection, but does not appear to correlate with herpes simplex viral reactivation in humans.